Personality, Preferred Leadership Style and Principal Preparation - Gill, Peggy B.; Linn, Genie B.; Sherman, Ross (Richtmann Publishing, 2012)
This study identifies the preferred leadership styles of students enrolled in principal preparation programs andcompares the styles identified by traditional public school teachers and charter school teachers who seek principal certification.Participative leadership and Goal Oriented leadership were identified as the predominant styles. Seventy-five per cent ofteachers of traditional public schools identified one of these styles and 81% of teachers from charter schools identified one ofthese styles indicating both groups have similar preferred styles. Surprisingly, few of the participants in either group of the studywere aligned with Visionary Leadership or Change Leadership. Although people have a preferred leadership style based onpersonality traits, it is possible to learn the skills needed for other leadership styles. The results of this study indicate emphasisshould be placed on developing visionary leadership skills and change leadership skills. Hoyle (2007) emphasized theimportance of understanding why some of our educational leadership program graduates fail to be successful in the field. Whileit is important to realize that school leaders must have good managerial skills as well as good leadership skills this researchindicates students come to leadership preparation programs with a predisposition to learn management skills. Based on thisresearch, it may be that educational leadership programs are not recognizing the need to provide specific learning approachesthat lead to the development of transformational leaders.